Flávio Lichtenfels Motta - Segawa, Hugo (Revista Thésis, 2017)
Professor Flávio Motta (1923-2016) was one of the founders of the Department of History of Architecture and Aesthetics of Project of the Faculty of Architecture and Urbanism of the University of São Paulo. His passing in July 2016 and the silence of academia motivated this introductory essay of his role in the formation of generations of architects of FAU USP, from the testimony of a former student who took the path in the field of History of Architecture.